Associations between emotional symptoms and self-reported aberrant driving behaviors in older adults. (June 2019) - Bernstein, John P.K.; DeVito, Alyssa; Calamia, Matthew
Highlights: Links between older adults' emotional symptoms and driving behaviors are explored. Emotional distress was broadly associated with aberrant driving behaviors. Greater suicidality and appetite loss predicted greater unintentional driving errors. Greater ill temper and appetite loss predicted greater intentional driving errors. Neither obsessions/fears nor well-being predicted aberrant driving behaviors. Abstract: Objective: To examine associations between internalizing symptoms and self-reported aberrant driving behaviors in a large sample (n = 341) of older adults (mean age = 62.6 years, SD = 4.8). Design: Cross-sectional survey. Results: Multiple regression analyses revealed that greater symptoms of emotional distress (i.e., higher scores on the Expanded Version of the Inventory of Depression and Anxiety Symptoms (IDAS-II) emotional distress composite) were associated with greater aberrant driving behaviors (i.e., higher scores on the Driving Behavior Questionnaire). In contrast, neither obsessions/fears nor emotional well-being were associated with greater aberrant driving behaviors. Follow-up regression analyses examining specific IDAS-II subscales revealed that greater suicidality, appetite gain, appetite loss, panic, and ill temper were associated with greater aberrant driving behaviors. Individuals reporting greater suicidality and appetite loss reported greater tendencies to unintentionally commit errors behind the wheel, while individuals reporting greater ill temper and appetite loss reported greater tendencies to intentionally engage in unsafe driving behaviors that may put other drivers in harm's way. Conclusion: Older adults reporting emotional distress may be at risk for engaging in aberrant driving behaviors. In particular, certain symptoms of emotional distress (e.g., suicidality, ill temper) are tied to higher rates of aberrant driving behaviors within this population.